Coughing May Lead to Spontaneous Chylothorax and Chylous Ascites - Adas, Gokhan (S. Karger AG, 2007)
Chylous ascites is a rare form of ascites resulting from the accumulation of lymph in the abdominal cavity. It is due to an interruption in the lymphatic system. Surgical management is indicated in cases of recurrence or failure after conservative treatment. We report a case of spontaneous chylous peritonitis after chylothorax, which is a rare clinical event. The primary reason was unclear and the outcome of medical and surgical treatment was successful.